2016
DOI: 10.1111/obr.12444
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and obesity in young subjects: a meta‐analysis

Abstract: Poor sleep quality seems to be associated with Ow/Ob, and some studies indicate this association to be independent of duration. Therefore, considering only sleep duration might not help in disentangling sleep-obesity association. However, this review is mostly composed of cross-sectional studies. Therefore, a causal link or the stability of the sleep quality and Ow/Ob association could not be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
231
5
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(266 citation statements)
references
References 49 publications
(207 reference statements)
17
231
5
13
Order By: Relevance
“…A second systematic review indicated that inadequate sleep measured as short duration and/or poor quality was linked to higher odds of obesity cross-sectionally. 23 The role of sleep quality, problems, and patterns and its relationship with children's health warrants further research. 22 Further, there may be interactions between sleep, screen-time, and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…A second systematic review indicated that inadequate sleep measured as short duration and/or poor quality was linked to higher odds of obesity cross-sectionally. 23 The role of sleep quality, problems, and patterns and its relationship with children's health warrants further research. 22 Further, there may be interactions between sleep, screen-time, and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that “diet-induced body-weight loss and successive body-weight maintenance contribute to sleep improvement” [6]. A recent study [7] investigated whether “enhancing children’s sleep may show promise in assisting with weight regulation.” Various reviews of cross-sectional and longitudinal studies have found evidence that short sleep duration and poor sleep quality are associated with general obesity and central obesity [8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…As described in the introduction, recent reviews have concluded that short sleep duration and poor sleep quality seems associated with childhood overweight and obesity [2,3]. However, so far only few studies have intervened on child sleep habits in relation to risk of obesity development [28,29,30], leaving rather little experience and inspiration from previous studies when designing a new intervention.…”
Section: Discussionmentioning
confidence: 99%
“…One alternate modifiable factor that has been found to lead to child overweight is sleep. In this regard, two recent meta-analyses have provided evidence that both short sleep duration and poor sleep quality seem associated with overweight in children and adolescents [2,3]. Poor sleep in toddlers and primary school children can impact child growth, and thereby later risk of obesity, via increased cortisol and decreased melatonin levels [4].…”
Section: Introductionmentioning
confidence: 99%